Single Atom Catalysts: Surface Reduction State Determines Stabilization and Incorporation of Rh on α‐Fe2O3(11¯02) (Adv. Mater. Interfaces 8/2021). Issue 8 (23rd April 2021) - Kraushofer, Florian; Resch, Nikolaus; Eder, Moritz; Rafsanjani‐Abbasi, Ali; Tobisch, Sarah; Jakub, Zdenek; Franceschi, Giada; Riva, Michele; Meier, Matthias; Schmid, Michael; Diebold, Ulrike; Parkinson, Gareth S.
Abstract : Rhodium atoms adsorbed on a model iron oxide surface sinter to nanoparticles already at room temperature. Redispersion into isolated single atoms is induced by oxygen annealing. The resulting atoms are incorporated in the first subsurface layer of the oxide, rather than the surface. More details can be found in article number 2001908 by Gareth S. Parkinson and co‐workers.